Evaluation Basic Online Training Program for Character-Building of Transportation Cadets at Indonesian Aviation School Banyuwangi - Rangga Handhika Putra; Arief Rusdyansyah; Agung Wahyu Wicaksono; Untung Lestari Nur Wibowo; Ikhwanul Qiram (Yayasan Ilomata, 2023)
The base period of character formation activities for transportation cadets is called